A ocupação do Congresso: contra o quê lutam os índios? - Capiberibe, Artionka; Bonilla, Oiara (Estudos Avançados, 2015)
This article explores the confrontation between the politics and economic model inherent in the present-day struggle of the indigenous people for recognition and guarantees of their way of life. Land is the basic issue around which tension with respect to the Indians cristalize. At the heart of the question are radically opposing models of the relationship between the forms of life on the planet (fauna, flora, humanity). This article focuses on the political confrontations between these models, shedding light on the Indian's struggle against agribusiness and its representatives in the National Congress, radically exposed when the Indians occupied the Federal Chamber of Deputies in April 2013. The objective is to highlight the contemporary importance of the normative field as a space to dispute the guarantee of rights, as well as the influence of indigenous political protagonism.